Reticulocyte hemoglobin content (CHr) untuk skrining defisiensi besi pada ibu hamil - Bambang Sasangka; Tri Ratnaningsih (Jurnal Gizi Klinik Indonesia, 2019)
Reticulocyte hemoglobin content (CHr) for iron deficiency screening in pregnant womenBackground: Anemia in pregnancy is a major public health problem in developing countries. In Indonesia, such anemia is generally caused by nutritional deficiencies, particularly iron deficiency. Iron deficiency screening is needed to prevent the development of iron-deficiency anemia in pregnant women that may affect the health of the mother and fetus.Objective: The study objective was to determine the diagnostic validity of reticulocyte hemoglobin content (CHr) for iron deficiency screening in pregnant women.Method: This research is analytic observational research with a cross-sectional design. The subjects were 73 pregnant women in Bantul district with various gestational ages. CHr was examined with an Advia 120 automatic hematology analyzer. Examination of ferritin as gold standard uses chemiluminescens method with Elecsys 1010 immunology analyzer. Table 2x2 is used to test several CHr values in the CHr range for women of reproductive age of 28.8 - 34.5 pg.Results: Based on ferritin <15 μg / L as a gold standard, 13 pregnant women were suffered from iron deficiency while others were normal.Conclusion: CHr at 30.7 pg cut off has a sensitivity of 92.31%; negative predictive value (NPV) 96.2%; and likelihood ratio (LR) produce conclusive changes in post-test probability. In this cut-off, CHr can be used as an iron deficiency screening test in pregnant women.